2014
DOI: 10.4236/acs.2014.43036
|View full text |Cite
|
Sign up to set email alerts
|

Water-Level Fluctuations of Urmia Lake: Relationship with the Long-Term Changes of Meteorological Variables (Solutions for Water-Crisis Management in Urmia Lake Basin)

Abstract: Urmia Lake in northwest of Iran, through the recent years has been extremely faced with the water crisis. Climate variations and anthropogenic impacts could be two main affiliated factors in this regard. We considered the long term data series of precipitation, temperature and evaporation in monthly and yearly scales in order to compare to water-level values of Urmia Lake. The statistics approaches such as: standard deviation, trend analysis, T test, Pearson and Spearman correlations, liner regression are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…This was mainly triggered by an uncontrolled growth of the irrigated area, accompanied by the extensive construction of reservoirs, and poor agricultural water use efficiency. Several studies base their conclusions on trend analysis of hydro-meteorological data sets 8,19,22,23 . While Jalili et al 19 and Khazaei et al 22 identified only weak correlations between meteorological variables and lake level and hence concluded that mainly anthropogenic changes caused the lake level decline, Alizadeh-Choobari et al 8 and Zoljoodi and Didevarasl 23 could identify more pronounced trends in climate variables, i.e.…”
mentioning
confidence: 99%
“…This was mainly triggered by an uncontrolled growth of the irrigated area, accompanied by the extensive construction of reservoirs, and poor agricultural water use efficiency. Several studies base their conclusions on trend analysis of hydro-meteorological data sets 8,19,22,23 . While Jalili et al 19 and Khazaei et al 22 identified only weak correlations between meteorological variables and lake level and hence concluded that mainly anthropogenic changes caused the lake level decline, Alizadeh-Choobari et al 8 and Zoljoodi and Didevarasl 23 could identify more pronounced trends in climate variables, i.e.…”
mentioning
confidence: 99%
“…The freshwater input to this lake comes from surface resources (17 permanent rivers and 12 seasonal rivers [50]), of which the Zarine, Simine, and Ajichai rivers provide the largest proportion. The water level in this lake started to decrease sharply from 1995 [50] and has registered negative trends since then [51].…”
Section: Study Areamentioning
confidence: 97%
“…Climate change in the Middle East (Akkermanns et al 2010;Peterson et al 1979;Dastorani et al 2011), especially in Iran has been reported by many authors (Kehl 2009;Mohammadi 2012;Farshad 2013;Amiri and Eslamian 2012;Schmidt et al 2011;Lateef 1988;Kehl et al 2009). Change in the water levels in the lakes around the world (Street and Grove 1979) as well as the Urmia lake (Zoljoodi and Didevarasl 2014;Jahanbakhsh, Adalatdost, and Tadayoni 2011;Mahmoei et al 2012), Sistan Playa (Jarahi and Nadalian 2013b;Vekerdy and Dost 2006;Smith 1974;Costantini and Tosi 1978), Hoze Soltan Playa (Huntington 1905) Haj-Ali-Qoli Playa (Jarahi and Nadalian 2013a;Mousavi et al 2013), Great Kavir Desert (Jarahi 2016;Jarahi, Naraghiaraghi, and Nadalian 2016), Zaribar Lake (Snyder et al 2001;Stevens, Wright, andIto 2001), Caspian Sea (Naderi Beni et al 2013;Ramezani et al 2008), and other places (in Iran) has been studied previously (Mehrshahi 2002;Roberts and Wright 1993;Ramesht 2001). Various extensive studies have been conducted about the ancient lakes in the world.…”
Section: Introductionmentioning
confidence: 94%